Analysis of Beginning Reading Difficulties among Second-Grade Elementary School Students in Muna Regency - Puput Albar; Kasmawati Kasmawati; La Sisi (CV. Gerasi Insan Nusantara, 2025)
This study aimed to examine the beginning reading abilities of second-grade students, identify the difficulties they experienced, and describe the efforts undertaken to address those difficulties. A qualitative descriptive approach was employed. The study was conducted among second-grade students at SD Negeri 9 Kabangka, located in Oensuli Village, Kabangka District, Muna Regency, during the second semester of the 2025/2026 academic year. Data were collected through observation, semi-structured interviews, and documentation. Data analysis followed the interactive model of Miles, Huberman, and Saldaña (2022), involving data collection, data condensation, data display, and conclusion drawing and verification. The findings showed that students' beginning reading abilities varied. While some students were able to read letters, syllables, words, and simple sentences relatively well, others experienced difficulties in recognizing and distinguishing letters, reading syllables fluently, pronouncing simple words accurately, and reading confidently in front of the class. The difficulties were influenced by internal and external factors, including limited interest and motivation to read, low self-confidence, insufficient reading practice at home, and limited parental assistance. Efforts to address these difficulties included individualized guidance, the use of engaging instructional media and methods, repeated reading practice, parental involvement, and continuous motivational support. The study concludes that beginning reading difficulties require systematic and sustained intervention involving teachers, students, and families to strengthen students' foundational literacy skills.